Determinan Penerapan Anggaran Berbasis Kinerja terhadap Akuntabilitas Kinerja Instansi Pemerintah di Kabupaten Blora - Santos, Fernando; Erry Andhaniwati (Al-Buhuts, 2024)
This study examines the effect of performance-based budgeting on the accountability of government agency performance in Blora Regency. It focuses on four variables: budget planning (X1), budget implementation (X2), budget reporting/accountability (X3), and performance evaluation (X4). The research utilizes a quantitative approach, with the population consisting of employees from government agencies in Blora Regency. A purposive sampling technique was used, selecting 98 employees involved in government budget preparation. Data were collected using questionnaires as the primary data source, which were distributed to respondents. Multiple linear regression analysis was conducted using Statistical Package for Social Science (SPSS) version 25. The results indicate that budget planning positively affects the accountability of government agency performance in Blora Regency. Additionally, budget implementation, budget reporting/accountability, and performance evaluation also positively influence the accountability of government agency performance in Blora Regency